Pengembangan Asesmen Kinerja pada Praktikum IPA Berbasis Pendekatan Saintifik Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VII SMP - Desak Nyoman Putriadi (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2020)
The purpose of this research was to produce a science practicum performance assessment instrument based on scientific approach that is valid, practical, and effective to improve the critical thinking ability of junior high school students. The type of this research is development research using model by Sugiono (2007) with modification. In this study, the author only made it to the 7th step, which is the Usage Trial step due to limited knowledge, time and cost. The steps of this development research include (1) data collection, (2) product design, (3) design validation, (4) design revision, (5) product testing, (6) product revision, (7) usage test. The average result for the validity test of the instruments is 91,3% and categorized as very valid and can be applied on learning activity after going through several revisions. From reliability test, the result is 0,89 and is categorized as very reliable because >0,7. While the result of practicality test for teachers is at 62% and is categorized as quite practical. From the pre-test and post-test grade of the students, the average grade of both are 24,87 and 70,36. Based on n-gain test, obtained n= 0,60 and categorized as effective. From the results, it can be concluded that the performance assessment instrument of science practicum based is very valid, quite practical and effective to increase students’ critical thinking skill.Keywords: performance assessment of science practicum, scientific approach, critical thinking.